Um caso de aprendizagem organizacional: exame conceitual e de aplicabilidade no contexto público - Scheidemantel, Ricardo Henrique (2002)
This research has a practice-oriented focus on the concept of Organizational Learning. The basic approach is a learning organization perspective, and some references to the concepts and concerns of organizational learning were included whenever necessary and proper. Organizational Learning is researched mainly from a management techniques and strategy point of view, with a smaller emphasis on the innovation and accumulation of technological capabilities and theoretical research points of view. A broad approach has been used, based mainly on the study of a successful case using action research in a private telecommunication company operating nationwide in Brazil. This study involved a small group, as it is common with pilot groups for learning organizations. The main purpose of this research is to provide a broad and updated survey about the idea of Organizational Learning. Results presented in the related literature are compared with findings from the field, and that literature is cited throughout the text. The interactions of Organizational Learning with the Brazilian context and with the public administration context are analyzed; important data, ranging from the historical origins and bases of the concept, to details of the activities in a real life learning organization, are shown. Some essential aspects, that should be considered or used when applying this type of management, are analyzed. The action research has shown a close proximity between Organizational Learning and a phenomenological perspective, servant leadership, and managerial model, respectively in the fields of philosophical approach, leadership, and management models.